Battery cell, battery device, and electric device
Patent Information
- Application Number
- CN202510479411.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本申请是鉴于上述课题而进行的,其目的在于,提供一种电池单体、电池装置及用电装置,本申请中的电池单体具有提高的首次库伦效率和改进的循环性能。
Smart Images

Figure CN122968211A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a battery cell, a battery device, and an electrical device. Background Technology
[0002] With the rapid development of technology, the performance requirements for batteries in various electronic devices and electric vehicles are becoming increasingly stringent, leading to growing attention on solid-state batteries using solid-state electrolytes. On one hand, solid-state electrolytes possess properties such as non-flammability, non-corrosiveness, and non-volatility, significantly improving safety. On the other hand, solid-state electrolytes are compatible with higher-voltage electrode materials, creating possibilities for increasing the energy density of solid-state batteries. Currently, with the application and promotion of solid-state batteries, the requirements for their initial coulombic efficiency and cycle performance are becoming increasingly stringent.
[0003] Therefore, how to achieve high initial coulombic efficiency and excellent cycle performance in solid-state batteries has become an urgent technical problem to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell, a battery device and an electrical device, wherein the battery cell of this application has improved initial coulombic efficiency and improved cycle performance.
[0005] To achieve the above objectives, a first aspect of this application provides a battery cell comprising a positive electrode sheet and an electrolyte membrane. The positive electrode sheet includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a sulfide electrolyte material, a binder, and a dispersant. Both the binder and the dispersant are chemically inert to the sulfide electrolyte material. The dispersant accounts for 0.05% to 1% of the mass of the positive electrode film layer.
[0006] In this application, since both the binder and dispersant are chemically inert to the sulfide electrolyte material, the sulfide electrolyte material can exist stably in the positive electrode film layer. This allows it to effectively form a continuous and stable ion transport path in the positive electrode film layer, improving the charge and discharge efficiency of the secondary battery. Furthermore, introducing a dispersant into the positive electrode film layer facilitates the uniform dispersion of the electrolyte material and binder. Uniform dispersion of the electrolyte material can construct a continuous ion transport path in the positive electrode sheet, which is beneficial for improving the initial coulombic efficiency of the battery cell. Uniform dispersion of the binder can improve the adhesion between the components in the positive electrode film layer, which is beneficial for improving the stability of the positive electrode film layer during long-term cycling, thus improving the cycle performance of the battery cell. Further, the addition of the dispersant provides excellent suspension and dispersion for the sulfide electrolyte material and binder components in the positive electrode film layer, thereby keeping the viscosity and filtration speed of the positive electrode slurry within a suitable range. High stability of the positive electrode slurry also helps improve the processing performance of the battery cell. Based on this, by controlling the mass ratio of the dispersant in the positive electrode film layer within the above range, the dispersion degree of the electrolyte material and binder is more appropriate, which is more conducive to optimizing the ion transport path and enhancing the bonding effect, thereby more conducive to improving the first coulombic efficiency and cycle performance of the battery cell.
[0007] In some embodiments, the dispersant comprises 0.25% to 0.6% by mass in the positive electrode film. This is more conducive to improving the initial coulombic efficiency and cycle performance of the secondary battery.
[0008] In some embodiments, the dispersant comprises a polyolefin. This is more conducive to improving the uniformity of binder distribution in the positive electrode film, thereby further improving the initial coulombic efficiency and cycle performance of the battery cell.
[0009] In some embodiments, the dispersant includes one or more of low-density polyethylene, polyisobutylene, and polyolefin elastomers. This is more conducive to improving the initial coulombic efficiency and cycle performance of the battery cell.
[0010] In some embodiments, the dispersant comprises low-density polyethylene, and the number-average molecular weight of the low-density polyethylene is 600,000 to 2.2 million. This is more conducive to improving the initial coulombic efficiency and cycle performance of the battery cell.
[0011] In some embodiments, the binder includes one or more of hydrogenated styrene-butadiene rubber, styrene-ethylene-butadiene block copolymers, styrene-isobutylene-styrene triblock copolymers, and styrene-ethylene-propylene-styrene block copolymers. These binders are beneficial for improving the adhesion between the components in the positive electrode film and for improving the adhesion between the positive electrode film and the positive electrode current collector, thereby improving the initial coulombic efficiency and cycle performance of the battery cell.
[0012] In some embodiments, the binder comprises hydrogenated styrene-butadiene rubber. This is more conducive to improving the initial coulombic efficiency and cycle performance of the battery cell.
[0013] In some embodiments, the degree of hydrogenation of the hydrogenated styrene-butadiene rubber is greater than or equal to 95%; and / or, the molar content of benzene rings in the hydrogenated styrene-butadiene rubber is 5% to 40%. This is beneficial for further improving the initial coulombic efficiency and cycle performance of the battery cell.
[0014] In some embodiments, the binder comprises 0.5% to 1.5% by mass in the positive electrode film. This allows for a balance between the initial coulombic efficiency, cycle performance, and energy density of the battery cell.
[0015] In some embodiments, the sulfide electrolyte material accounts for 5% to 20% of the mass of the positive electrode film. This facilitates the formation of a suitable, continuous, and stable ion transport path in the positive electrode film, reduces interfacial impedance, and improves the charge and discharge efficiency of the secondary battery.
[0016] In some embodiments, the positive electrode film layer further includes a positive electrode active material; the positive electrode active material accounts for 70% to 88% of the mass of the positive electrode film layer. This is beneficial for improving the energy density of the battery cell.
[0017] In some embodiments, the positive electrode film layer further includes a conductive agent; the conductive agent accounts for 0.5% to 2% of the mass of the positive electrode film layer. This is beneficial for increasing the loading of the positive electrode sheet and further for improving the energy density of the secondary battery.
[0018] In some embodiments, the battery cell further includes a negative electrode; the electrolyte membrane is located between the positive electrode and the negative electrode.
[0019] A second aspect of this application provides a battery device comprising the battery cell described in the first aspect.
[0020] A third aspect of this application provides an electrical device, which includes the battery device described in the second aspect. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application.
[0022] Figure 2 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown.
[0023] Figure 3This is a schematic diagram of a battery module according to one embodiment of this application.
[0024] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0025] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0026] Figure 6 This is a schematic diagram of a battery device used as a power source according to an embodiment of this application.
[0027] Explanation of reference numerals in the attached figures:
[0028] 1 Battery pack; 2 First housing; 3 Second housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0029] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0030] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0032] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0033] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0034] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0035] Unless otherwise specified, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in this application.
[0036] Sulfide solid electrolytes (SSEs) are widely used in membranes due to their high ionic conductivity, ideal mechanical properties, and better interfacial contact with active materials. Currently, the mainstream membrane deposition process for SSEs is the wet process. The wet process typically involves mixing solvents, binders, and conductive agents with the SSE and then coating the mixture to form a membrane. It offers advantages such as low cost and high efficiency. However, in the wet process, because SSEs have good compatibility with nonpolar or weakly polar solvents, based on the principle of "like dissolves like," the binder usually needs to be nonpolar or low-polar. However, nonpolar or low-polar binders lack functional groups or atoms that donate lone pairs of electrons, and can only interact with the SSE particles through weak intermolecular forces. This results in poor adhesion between components in the membrane and between the membrane and the current collector, thus affecting the battery's processing performance, initial coulombic efficiency, and cycle performance.
[0037] In related technologies, the adhesion between components in the membrane and between the membrane and the current collector is improved by selecting a medium polarity binder. However, this will affect the stability of the sulfide solid electrolyte, which in turn will deteriorate the battery's initial coulombic efficiency and cycle performance.
[0038] Based on this, this application proposes a novel battery cell, battery device, and power supply device. The battery cell of this application exhibits high initial coulombic efficiency and improved cycle performance. The following provides a more detailed description of this application and its optional embodiments.
[0039] battery cell
[0040] The first aspect of this application provides a battery cell, including a positive electrode sheet and an electrolyte membrane. The positive electrode sheet includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a sulfide electrolyte material, a binder, and a dispersant. Both the binder and the dispersant are chemically inert to the sulfide electrolyte material. The mass percentage of the dispersant in the positive electrode film layer is 0.05% to 1%.
[0041] In this application, since both the binder and dispersant are chemically inert to the sulfide electrolyte material, the sulfide electrolyte material can exist stably in the positive electrode film layer. This allows it to effectively form a continuous and stable ion transport path in the positive electrode film layer, improving the charge and discharge efficiency of the secondary battery. Furthermore, introducing a dispersant into the positive electrode film layer facilitates the uniform dispersion of the electrolyte material and binder. Uniform dispersion of the electrolyte material can construct a continuous ion transport path in the positive electrode sheet, which is beneficial for improving the initial coulombic efficiency of the battery cell. Uniform dispersion of the binder can improve the adhesion between the components in the positive electrode film layer, which is beneficial for improving the stability of the positive electrode film layer during long-term cycling, thus improving the cycle performance of the battery cell. Further, the addition of the dispersant provides excellent suspension and dispersion for the sulfide electrolyte material and binder components in the positive electrode film layer, thereby keeping the viscosity and filtration speed of the positive electrode slurry within a suitable range. High stability of the positive electrode slurry also helps improve the processing performance of the battery cell. Based on this, by controlling the mass ratio of the dispersant in the positive electrode film layer within the above range, the dispersion degree of the electrolyte material and binder is more appropriate, which is more conducive to optimizing the ion transport path and enhancing the bonding effect, thereby more conducive to improving the first coulombic efficiency and cycle performance of the battery cell.
[0042] In some embodiments, the dispersant comprises 0.25% to 0.6% by mass in the positive electrode film. This is more beneficial for improving the initial coulombic efficiency and cycle performance of the secondary battery. Exemplarily, the dispersant comprises a value within a range of 0.05%, 0.1%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or any combination thereof in the positive electrode film.
[0043] Sulfide electrolyte materials are highly sensitive to substances containing polar functional groups because the isolated electron pairs in polar functional groups attack the electron acceptors in the sulfide electrolyte material, while the isolated electron pairs on the sulfur atoms in the sulfide electrolyte material attack the electron-deficient atoms in the polar functional groups. These reactions lead to the structural disintegration of the sulfide electrolyte material. In this application, both the binder and dispersant are chemically inert to the sulfide electrolyte material. That is, at room temperature, such as 25±5℃, when the binder or dispersant is mixed with the sulfide electrolyte material and a non-polar or low-polarity solvent, the chemical reaction between the binder or dispersant and the sulfide electrolyte material is inert; that is, common chemical reactions such as acid-base neutralization, redox reactions, and complexation will not occur between the binder or dispersant and the sulfide electrolyte material.
[0044] The non-polar or low-polarity solvents mentioned above refer to solvents with a polarity parameter not exceeding 4. The polarity parameter is used to characterize the polarity of a solvent; the larger the polarity parameter, the greater the polarity of the solvent, and the lower the polarity parameter, the less polar the solvent. Polarity parameters can be obtained by consulting reference books; solvents with a polarity parameter not exceeding 4 are generally considered low-polarity solvents.
[0045] In this application, neither the binder nor the dispersant reacts chemically with the sulfide electrolyte material; that is, neither the binder nor the dispersant contains a large number of polar functional groups. Specifically, the binder in this application is a non-polar binder or a low-polar binder, and the dispersant is a non-polar dispersant or a low-polar dispersant.
[0046] In some embodiments, the dispersant includes polyolefins. Polyolefins, due to the significant steric hindrance of their saturated carbon-carbon single bonds and nonpolar alkyl groups on their molecular chains, can effectively prevent the aggregation of components in the positive electrode film layer due to van der Waals forces or electrostatic forces. This is beneficial for improving the uniformity of binder distribution in the positive electrode film layer, thereby further improving the initial coulombic efficiency and cycle performance of the battery cell.
[0047] In some embodiments, the dispersant includes one or more of low-density polyethylene, polyisobutylene, and polyolefin elastomers. These dispersants effectively prevent the aggregation of components in the positive electrode film layer due to van der Waals forces or electrostatic forces, which helps to further improve the uniformity of the binder distribution in the positive electrode film layer, thereby further improving the initial coulombic efficiency and cycle performance of the battery cell.
[0048] In some embodiments, the dispersant comprises low-density polyethylene with a number-average molecular weight of 600,000 to 2,200,000. This facilitates further improvement in the dispersion of the electrolyte material and the binder, thereby optimizing ion transport pathways, enhancing adhesion, and ultimately improving the initial coulombic efficiency and cycle performance of the battery cell. Exemplarily, the number-average molecular weight of the low-density polyethylene is a value within the range of 600,000, 800,000, 1,000,000, 1,200,000, 1,500,000, 1,800,000, 2,000,000, 2,200,000, or any combination thereof.
[0049] In this application, low-density polyethylene (LDPE) is a polyethylene resin produced by free radical polymerization of ethylene monomers under high temperature and pressure, with a density of 0.91 g / cm³. 3 Up to 0.925 g / cm 3 .
[0050] In this application, the number-average molecular weight of low-density polyethylene has a meaning known in the art and can be tested using instruments and methods known in the art. For example, it can be tested by gel permeation chromatography (GPC).
[0051] In some embodiments, the binder includes one or more of hydrogenated styrene-butadiene rubber, styrene-ethylene-butadiene block copolymers, styrene-isobutylene-styrene triblock copolymers, and styrene-ethylene-propylene-styrene block copolymers. Optionally, the binder includes hydrogenated styrene-butadiene rubber. The above-mentioned binders are non-polar or low-polar binders, which can be stably present in the sulfide electrolyte material system. This is beneficial for improving the adhesion between the components in the positive electrode film and the adhesion between the positive electrode film and the positive electrode current collector, thereby improving the initial coulombic efficiency and cycle performance of the battery cell.
[0052] In some embodiments, the degree of hydrogenation of the hydrogenated styrene-butadiene rubber (SBR) is greater than or equal to 95%. Optionally, the degree of hydrogenation of the SBR is 97% to 100%. A higher degree of hydrogenation of the SBR results in better oxidation resistance, which helps reduce the oxidative degradation of the binder during cycling, thereby improving the initial coulombic efficiency and cycle performance of the battery cell. Exemplarily, the degree of hydrogenation of the SBR is a value within a range of 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 100%, or any combination thereof.
[0053] The "degree of hydrogenation" of hydrogenated styrene-butadiene rubber (SBR) refers to the extent to which the double bonds in the butadiene unit are saturated with hydrogen, i.e., degree of hydrogenation = number of hydrogenated butadiene double bonds / total number of double bonds in the initial butadiene. In this application, the degree of hydrogenation of SBR can be determined by detecting the characteristic absorption peaks of carbon-carbon double bonds in hydrogenated SBR using infrared spectroscopy and by analyzing the changes in the intensity of these characteristic absorption peaks.
[0054] In some embodiments, the molar content of benzene rings in hydrogenated styrene-butadiene rubber (SBR) is 5% to 40%. Optionally, it is 10% to 20%. The benzene rings in SBR primarily provide the hardness of the polymer. When the content of benzene rings in SBR is within the above range, the hardness and adhesion properties of SBR are within a suitable range. A suitable hardness range is beneficial for the coating and cold pressing process of the positive electrode sheet, i.e., it is beneficial for improving the processing performance of the battery cell. A suitable adhesion property range is beneficial for further improving the adhesion of the positive electrode film, thereby further improving the initial coulombic efficiency and cycle performance of the battery cell. Exemplarily, the molar content of benzene rings in SBR is a value within the range of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or any combination thereof.
[0055] In this application, since hydrogen atoms in different chemical environments will produce different chemical shifts in the 1H NMR spectrum, aromatic hydrogens on the benzene ring usually appear in the region of 6.5ppm to 7.5ppm, and hydrogens on the saturated hydrocarbon chain appear between 0.5ppm and 2.5ppm. Therefore, the molar content of the benzene ring in hydrogenated styrene-butadiene rubber can be determined by 1H NMR spectrum. Specifically, 20mg of hydrogenated styrene-butadiene rubber is dissolved in 1mL of deuterated dichloromethane, and NMR is performed to obtain the corresponding NMR spectrum. The area A1 of the peaks (hydrogen peaks of aromatic rings) in the 6.5ppm to 7.5ppm region is calculated, and the area A2 of the peaks (hydrogen peaks of alkyl chains) in the 0.5ppm to 2.5ppm region is calculated. The molar ratio of the benzene ring B% = A1 / (A1+A2)*(8 / 5), where 5 is the number of hydrogens in the benzene ring and 8 is the number of hydrogens in the styrene monomer.
[0056] In some embodiments, the binder comprises 0.5% to 1.5% by mass in the positive electrode film layer, optionally 1.0% to 1.5%. A binder mass percentage within this range can improve the adhesion between components in the positive electrode film layer and the adhesion between the positive electrode film layer and the positive electrode current collector without affecting the energy density of the battery cell, thereby achieving a balance between the initial coulombic efficiency, cycle performance, and energy density of the battery cell. Exemplarily, the binder mass percentage in the positive electrode film layer is a value within the range of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any combination thereof.
[0057] In some embodiments, the sulfide electrolyte material constitutes 5% to 20% of the positive electrode film by mass. Optionally, it is 10% to 15%. A mass percentage of the sulfide electrolyte material in the positive electrode film within this range is beneficial for forming a suitable, continuous, and stable ion transport path in the positive electrode film, reducing interfacial impedance, and improving the charge-discharge efficiency of the secondary battery. Exemplarily, the mass percentage of the sulfide electrolyte material in the positive electrode film is a value within a range of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any combination thereof.
[0058] In some embodiments, the sulfide electrolyte material includes LiPS5Cl, LiPS5Br, Li2S-P2S5, Li4GeS4, and Li 10 GeS 12 Li3PS4, Li7P3S 11 One or more of them.
[0059] In some embodiments, the positive electrode film layer further includes a positive electrode active material; the mass percentage of the positive electrode active material in the positive electrode film layer is 70% to 88%, optionally 78% to 85%. A mass percentage of the positive electrode active material in the positive electrode film layer within the above range is beneficial for improving the energy density of the battery cell. Exemplarily, the mass percentage of the positive electrode active material in the positive electrode film layer is a value within a range of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, or any combination thereof.
[0060] In some embodiments, the positive electrode active material may be a positive electrode active material known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.10 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0061] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., before feeding. When the positive electrode active material is applied to the battery system, the molar Li content changes after charge-discharge cycles.
[0062] In the examples of positive electrode active materials in this application, the molar content of oxygen is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of oxygen will fluctuate.
[0063] In some embodiments, the positive electrode film layer further includes a conductive agent; the conductive agent accounts for 0.5% to 2% of the mass of the positive electrode film layer, optionally 1% to 1.5%. A mass percentage of the conductive agent in the positive electrode film layer within the above range reflects a relatively low content of the conductive agent in the positive electrode film layer, which is beneficial for increasing the loading of the positive electrode sheet and further beneficial for increasing the energy density of the secondary battery. For example, the mass percentage of the conductive agent in the positive electrode film layer is a value within the range of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or any combination thereof.
[0064] In some implementations, the battery cell can be a secondary battery, which refers to a battery cell that can be recharged after discharge to activate the active materials and continue to be used.
[0065] In some embodiments, a battery cell includes a casing and electrode assemblies. The casing is the outer protective shell of the battery cell, with an internal cavity for encapsulating components such as the electrode assemblies. The electrode assemblies are the components within the battery cell where electrochemical reactions occur. The electrode assemblies are typically stacked along the thickness direction (stack direction) of the battery cell. The electrode assemblies include a positive electrode, a negative electrode, and an electrolyte membrane. During the charging and discharging process of the battery cell, active ions (e.g., lithium ions) repeatedly insert and extract between the positive and negative electrode plates. The electrolyte membrane, disposed between the positive and negative electrode plates, prevents short circuits between the positive and negative electrodes while allowing active ions to pass through.
[0066] In some embodiments, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0067] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0068] In some embodiments, the positive electrode sheet can be formed by: adding a dispersant to a weakly polar solvent, and then maintaining the solution at 60°C to 100°C for 4 to 24 hours, allowing the dispersant, high molecular weight polyethylene, to dissolve in the weakly polar solvent to form a mixed solution; then, the positive electrode active material LiNi... 0.8 Co 0.1 Mn 0.1 O2, sulfide solid electrolyte material Li6PS5Cl, conductive agent vapor-grown carbon fiber, and binder hydrogenated styrene-butadiene rubber are added to the above mixed solution and mixed evenly to form a positive electrode slurry with a solid content of 45% to 80%. The weight ratio of positive electrode active material: sulfide electrolyte material: conductive agent: binder: dispersant in the positive electrode slurry is (70% to 88%): (5% to 20%): (0.5% to 2%): (0.5% to 1.5%): (0.05% to 1%). The weakly polar solvent includes pseudotrimethylbenzene or ester solvents. Then, the positive electrode slurry is evenly coated on both sides of aluminum foil, and after cutting, the positive electrode sheet is obtained.
[0069] In some embodiments, the battery cell also includes a negative electrode; an electrolyte membrane is located between the positive and negative electrode.
[0070] In some embodiments, the electrolyte membrane may also include a gel electrolyte membrane, a semi-solid electrolyte membrane, or a solid electrolyte membrane.
[0071] In some embodiments, the gel electrolyte membrane includes at least one of a composite gel polymer electrolyte membrane and a porous colloidal polymer electrolyte membrane.
[0072] In some embodiments, the semi-solid electrolyte membrane includes at least one of a gel polymer electrolyte membrane, a polymer electrolyte membrane, and an aerogel electrolyte membrane.
[0073] In some embodiments, the solid electrolyte membrane includes at least one of sulfide solid electrolyte membrane, oxide solid electrolyte membrane, and halide solid electrolyte membrane.
[0074] In some embodiments, the solid electrolyte membrane can be obtained by mixing one or more of the following: a binary compound such as Li6PS5Cl, Li2S-GeS2, Li2S-P2S5, Li2S-SiS2, and a ternary compound such as Li2S-MeS2-P2S5 (Me = Si, Ge, Sn, Al, etc.) with a binder such as PTFE, polyvinylidene fluoride, ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin, and then rolling it out.
[0075] In some embodiments, the electrolyte membrane includes a solid electrolyte material and a binder; the binder accounts for 1% to 10% of the mass of the electrolyte membrane, and the solid electrolyte material accounts for 90% to 99% of the mass of the electrolyte membrane.
[0076] In some embodiments, the binder in the electrolyte membrane can be a non-polar or low-polar binder used in the positive electrode membrane layer of this application, such as one or more of hydrogenated styrene-butadiene rubber, styrene-ethylene-butadiene block copolymers, styrene-isobutylene-styrene triblock copolymers, and styrene-ethylene-propylene-styrene block copolymers. Optionally, the binder includes hydrogenated styrene-butadiene rubber; more preferably, the molar content of benzene rings in the hydrogenated styrene-butadiene rubber is 5% to 40%, and the degree of hydrogenation of the hydrogenated styrene-butadiene rubber is greater than or equal to 95%.
[0077] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0078] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0079] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0080] In some embodiments, the negative electrode active material can be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0081] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0082] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0083] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0084] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0085] In some embodiments, a solid electrolyte used to form the electrolyte layer is added to the model battery and subjected to a first cold pressing treatment; a positive electrode is added to one side of the model battery and subjected to a second cold pressing treatment; and a negative electrode is added to the other side of the model battery and subjected to a third cold pressing treatment, thus obtaining a single battery cell.
[0086] In some implementations, the positive electrode, negative electrode, and electrolyte membrane can be fabricated into an electrode assembly using a stacking process.
[0087] In some embodiments, the casing of the battery cell can be a rigid casing, such as a hard plastic casing, an aluminum casing, or a steel casing. The outer packaging of the battery cell can also be a soft package, such as a pouch. The material of the soft package can be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0088] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.
[0089] In some implementations, refer to Figure 2The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0090] Battery device
[0091] A second aspect of this application provides a battery device, which may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells as described in the first aspect, and the multiple battery cells are connected in series, parallel, or mixed connections via a busbar.
[0092] In some implementations, a battery cell assembly is typically formed by arranging multiple battery cells.
[0093] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.
[0094] As an example, the battery cell assembly can be a battery module, which can be housed in a housing by fixing the battery module in the housing.
[0095] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.
[0096] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.
[0097] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.
[0098] In some implementations, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0099] In some implementations, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.
[0100] The technical solutions described in the embodiments of this application are applicable to various electrical devices that use individual battery cells, such as mobile phones, portable devices, laptops, electric vehicles, electric toys, power tools, vehicles, ships, and spacecraft. For example, spacecraft include airplanes, rockets, space shuttles, and spacecraft.
[0101] Figure 3 This is battery module 4 as an example. (See reference...) Figure 3 In the battery module 4, multiple battery cells 5 can be arranged sequentially along the length of the battery module 4. Of course, they can also be arranged in any other way. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0102] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0103] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes a first housing 2 and a second housing 3. The first housing 2 can cover the second housing 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0104] Electrical appliances
[0105] A third aspect of the embodiments of this application also provides an electrical device, which will be described below with appropriate reference to the accompanying drawings.
[0106] The electrical device mentioned in the embodiments of this application includes the battery device provided in the second aspect of this application. The battery device can be the power source of the electrical device or the energy storage unit of the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0107] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0108] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0109] Example
[0110] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0111] Example 1
[0112] Preparation of battery cells:
[0113] 1) Preparation of positive electrode sheet
[0114] A certain amount of dispersant low-density polyethylene (density is 0.92 g / cm³) is added. 3 The mixture was added to the weakly polar solvent pseudotrimethylbenzene and then kept at 80°C for 8 hours to allow the dispersant, high molecular weight polyethylene, to dissolve in the pseudotrimethylbenzene, forming a mixed solution. Then, the positive electrode active material, LiNi... 0.8 Co 0.1 Mn 0.1 O2, sulfide solid electrolyte material Li6PS5Cl, conductive agent vapor-grown carbon fiber, and binder hydrogenated styrene-butadiene rubber are added to the above mixed solution and mixed evenly to form a positive electrode slurry with a solid content of 50%. The positive electrode active material LiNi in the positive electrode slurry... 0.8 Co 0.1 Mn 0.1The weight ratio of O2, sulfide solid electrolyte material Li6PS5Cl, conductive agent vapor-grown carbon fiber, binder hydrogenated styrene-butadiene rubber, and dispersant high molecular weight polyethylene is 82:15:1.5:1:0.5; the degree of hydrogenation of hydrogenated styrene-butadiene rubber is 95%, the content of benzene rings in hydrogenated styrene-butadiene rubber is 15%, and the molecular weight of low-density polyethylene is 1.2 million; then the positive electrode slurry is coated on the positive electrode current collector aluminum foil to form a positive electrode film layer, and after drying and cold pressing, the positive electrode sheet is obtained.
[0115] 2) Preparation of negative electrode sheet
[0116] The negative electrode material, silicon-carbon composite material (silicon content of 18% by mass), binder, polyacrylic acid (PAA), and conductive agent, carbon nanotubes, are dissolved in deionized water at a weight ratio of 97:2:1 and thoroughly mixed to form a negative electrode slurry. The negative electrode slurry is then coated onto a copper foil current collector to form a negative electrode film. After drying and cold pressing, a negative electrode sheet is obtained.
[0117] 3) Preparation of electrolyte membrane
[0118] Electrolyte material Li6PS5Cl and binder polyacrylate were weighed and mixed in a mass ratio of 98:2 and added to a weakly polar solvent, pseudotrimethylbenzene, to prepare an electrolyte slurry. The electrolyte slurry was then coated onto both sides of the negative electrode sheet prepared above, with a coating thickness of 20 μm. After cutting, a negative electrode sheet with an electrolyte membrane was obtained.
[0119] 4) Assembly of individual battery cells
[0120] In an argon-filled glove box, the positive electrode is placed on both sides of the negative electrode containing the electrolyte membrane, sealed in an aluminum-plastic bag, and then isostatically pressed at 80°C and 500MPa for 10 minutes to prepare a battery cell.
[0121] Battery cell performance testing
[0122] (1) First Coulomb efficiency test
[0123] At 25°C, the prepared battery cell was charged at a constant current rate of 0.33C to 4.2V, and the charging capacity D1 was recorded. After standing for 10 minutes, the battery cell was discharged at a constant current rate of 0.33C to 2.8V, and the discharge capacity D0 was recorded. The initial coulombic efficiency (%) of the battery cell = D0 / D1 × 100%. The test results are recorded in Table 1 below.
[0124] (2) Cyclic performance test
[0125] At 25°C, the prepared battery cell is charged at a constant current rate of 0.33C to 4.2V, then charged at a constant voltage of 4.2V to 0.05C, and discharged at 0.33C to 2.8V, which is the first cycle. The discharge capacity of the first cycle is recorded as C0. The above steps are repeated for 400 cycles, and the discharge capacity of the 400th cycle is recorded as Cn.
[0126] The capacity retention rate after 400 cycles is (Cn / C0)*100%, and the test results are recorded in Table 2 below.
[0127] Examples 2-5
[0128] Battery cells were prepared using the same method as in Example 1, except that the types and contents of each component in the positive electrode film were adjusted according to Table 1 below.
[0129] In Example 2, the dispersant was ultra-high molecular weight polyethylene (UHMWPE), which has a molecular weight of 2 million.
[0130] Comparative Example 1
[0131] Battery cells were prepared using the same method as in Example 1, except that the positive electrode slurry did not contain a dispersant, and the mass ratio of the positive electrode active material, sulfide electrolyte material, conductive agent, and binder in the positive electrode slurry was 82:15:1.5:1.5.
[0132] Comparative Example 2
[0133] Battery cells were prepared using the same method as in Example 1, except that the mass ratio of positive electrode active material, sulfide electrolyte material, conductive agent, binder and dispersant in the positive electrode slurry was 81.5:15:1.5:0.8:1.2.
[0134] Table 1 below shows the relevant parameters of the positive electrode film in Examples 1 to 5 and Comparative Examples 1 and 2. Table 2 below shows the performance test results of the battery cells prepared in Examples 1 to 5 and Comparative Examples 1 and 2.
[0135] Table 1
[0136]
[0137] Table 2
[0138]
[0139] As can be seen from Tables 1 and 2, compared with Comparative Example 1 (no dispersant in the positive electrode film) and Comparative Example 2 (the content of dispersant in the positive electrode film is greater than 1%), in Examples 1 to 5, by controlling the positive electrode film to include sulfide electrolyte material, binder and dispersant, and controlling the mass ratio of dispersant to be in the range of 0.05% to 1%, the initial coulombic efficiency and cycle performance of the battery cell can be significantly improved.
[0140] In Comparative Example 1, since no dispersant is present, the dispersion uniformity of the electrolyte material and binder is poor, which is detrimental to the first coulombic efficiency and cycle performance of the battery cell. In Comparative Example 2, since the dispersant is electrochemically inert and has no ability to conduct lithium ions, its content is too high, which will deteriorate the first coulombic efficiency and cycle performance of the battery cell.
[0141] Examples 6-12
[0142] Battery cells were prepared using the same method as in Example 1, except that the types of dispersants and binders in the positive electrode film were adjusted according to Table 3 below;
[0143] In Example 6, the molar content of benzene rings in the hydrogenated styrene-butadiene rubber binder is 5%.
[0144] In Example 7, the molar content of benzene rings in the hydrogenated styrene-butadiene rubber adhesive is 40%.
[0145] In Example 8, the binder was a block copolymer of styrene-ethylene-butadiene;
[0146] In Example 9, the binder was a styrene-isobutylene-styrene triblock copolymer;
[0147] In Example 10, the binder was a styrene-ethylene-propylene-styrene block copolymer;
[0148] In Example 11, the dispersant was polyisobutylene, and the molecular weight of polyisobutylene was 700,000.
[0149] In Example 12, the dispersant was a polyolefin elastomer with a molecular weight of 1.1 million.
[0150] Table 3 below shows the relevant parameters of the positive electrode film in Examples 6 to 12 and the performance test results of the individual cells. Additionally, for ease of comparison, the relevant parameters from Example 1 are also shown.
[0151] Table 3
[0152]
[0153] As shown in Table 3, when the binder is selected from any one of hydrogenated styrene-butadiene rubber, styrene-ethylene-butadiene block copolymer, styrene-isobutylene-styrene triblock copolymer, or styrene-ethylene-propylene-styrene block copolymer; or when the binder is selected from hydrogenated styrene-butadiene rubber and the molar content of benzene rings in the hydrogenated styrene-butadiene rubber is 5% to 40%; or when the dispersant is selected from any one of low-density polyethylene, polyisobutylene, or polyolefin elastomer, the initial coulombic efficiency and cycle performance of the battery cell can be significantly improved. In Example 6, due to the low molar content of benzene rings in the hydrogenated styrene-butadiene rubber, the adhesive strength of the binder is relatively low, and the cycle performance of the battery cell in Example 1 is slightly lower. In Example 7, due to the high molar content of benzene rings in the hydrogenated styrene-butadiene rubber, the brittleness of the positive electrode sheet increases, and therefore, it is easy to shed powder during cycling, resulting in a slight decrease in the cycle performance of the battery cell in Example 1.
[0154] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A battery cell, characterized in that, It includes a positive electrode sheet and an electrolyte membrane sheet, wherein the positive electrode sheet includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector; The positive electrode film layer includes a sulfide electrolyte material, a binder, and a dispersant; Both the binder and the dispersant are chemically inert to the sulfide electrolyte material; The dispersant comprises 0.05% to 1% by mass in the positive electrode film.
2. The battery cell according to claim 1, characterized in that, The dispersant comprises 0.25% to 0.6% by mass in the positive electrode film.
3. The battery cell according to claim 1 or 2, characterized in that, The dispersant includes polyolefins.
4. The battery cell according to any one of claims 1 to 3, characterized in that, The dispersant includes one or more of low-density polyethylene, polyisobutylene, and polyolefin elastomers.
5. The battery cell according to any one of claims 1 to 4, characterized in that, The dispersant includes low-density polyethylene, and the number average molecular weight of the low-density polyethylene is 600,000 to 2,200,000.
6. The battery cell according to any one of claims 1 to 5, characterized in that, The adhesive includes one or more of hydrogenated styrene-butadiene rubber, styrene-ethylene-butadiene block copolymer, styrene-isobutylene-styrene triblock copolymer, and styrene-ethylene-propylene-styrene block copolymer.
7. The battery cell according to any one of claims 1 to 6, characterized in that, The adhesive includes hydrogenated styrene-butadiene rubber.
8. The battery cell according to claim 7, characterized in that, The degree of hydrogenation of the hydrogenated styrene-butadiene rubber is greater than or equal to 95%; and / or, The molar content of benzene rings in the hydrogenated styrene-butadiene rubber is 5% to 40%.
9. The battery cell according to any one of claims 1 to 8, characterized in that, The binder accounts for 0.5% to 1.5% of the mass of the positive electrode film.
10. The battery cell according to any one of claims 1 to 9, characterized in that, The sulfide electrolyte material accounts for 5% to 20% of the mass of the positive electrode film.
11. The battery cell according to any one of claims 1 to 10, characterized in that, The positive electrode film layer also includes a positive electrode active material; The positive electrode active material accounts for 70% to 88% of the mass of the positive electrode film.
12. The battery cell according to any one of claims 1 to 11, characterized in that, The positive electrode film layer also includes a conductive agent; The conductive agent accounts for 0.5% to 2% of the mass of the positive electrode film.
13. The battery cell according to any one of claims 1 to 12, characterized in that, The battery cell also includes a negative electrode sheet; The electrolyte membrane is located between the positive electrode and the negative electrode.
14. A battery device, characterized in that, Includes the battery cell according to any one of claims 1 to 13.
15. An electrical appliance, characterized in that, Includes the battery device as described in claim 14.